UK endoscopy trainees provide a significant quantity of service delivery. (13th March 2011) - Griffiths, L P; Dowler, K; Valori, R; Dunckley, P
Abstract : Introduction: In September 2009, the JAG Endoscopy Training System (JETS) e-portfolio was launched. Since its release, over 75% of UK trusts have set the system up and over 70 000 procedures logged by trainees. Within the JETS e-portfolio, trainees record their data under pre-defined lists. These are dedicated service lists (reduced points and/or tailored case mix), ad-hoc training lists (training occurring on a standard service list) or service lists. With the European Working Time Directive, trainees have less opportunity for endoscopy training. Furthermore, in a cash-strapped NHS, training may become a low priority over service delivery. We studied the proportion of endoscopies performed on each of the list types by trainees to assess when trainees start to provide service lists within the NHS. Methods: All endoscopy data from the JETS e-portfolio from September 2009 to 30 October 2010 were analysed. Results: There were 70 499 procedures from 16 433 procedure lists. All non-trainee roles were then excluded, leaving 60 124 endoscopies performed by trainees, and of these, 22 358 (37%) were on service lists. 34 186 endoscopies were performed by registrar-level doctors and 9726 (28%) of these were on service lists. Of these, gastroenterology registrars did 29 876, of which 8686 on service lists (29%) and GI surgical registrars did 4310, of which 1040 were on service lists (24%) (Figure 1 ). The remaining 25 938 endoscopies, of which 12 632 were service (47%), were performed by others such as associate specialists and nurse endoscopists. Conclusion: UK trainee endoscopists contribute towards a large volume of service provision; in fact by year 5, gastroenterology registrars perform the majority of their endoscopies on service lists. This data shows that hospital trusts should prioritise endoscopy training. High quality training will result in competent, experienced, independent trainee endoscopists who can support the service of the trust in which they work and gain further valuable experience.